Environmental filtering drives assembly of diatom communities over evolutionary time‐scales - Elena Jovanovska; Torsten Hauffe; Björn Stelbrink; Aleksandra Cvetkoska; Zlatko Levkov; Bernd Wagner; Jack H. Lacey; Nadja Ognjanova‐Rumenova; Paul B. Hamilton; Karen M. Brandenburg; Christian Albrecht; Thomas Wilke (Global Ecology and Biogeography, 2022)
Aim Ecological communities are structured through the interplay of deterministic assembly processes such as competition and environmental filtering. Whereas the drivers of spatial community structure are frequently studied in extant communities, little is known about the relative importance of assembly processes in response to environmental factors over evolutionary time‐scales. Here, we use an integrative framework to unravel community assembly processes since the inception of a long‐lived lake ecosystem. Location Lake Ohrid. Time period From lake formation 1.36 million years ago to the present. Major taxa studied Planktonic diatoms. Methods We constructed a dated phylogeny of extant and extinct diatoms and collected trait data for 380 fossil communities to quantify phylogenetic community structure and functional richness and to determine the relative importance of deterministic assembly processes over time. We then used regression analysis to correlate the phylogenetic community structure with palaeoenvironmental and intrinsic biological predictors and to identify primary drivers of assembly processes. Results Our results suggest a dense packing of niche space with higher species richness and co‐occurrence of closely related species. There are only two short episodes in the very recent past dominated by distantly related taxa. We found distinct changes in phylogenetic community structure upon speciation or extinction events and an increase in mean community relatedness over time. Main conclusions Our finding of closely related co‐occurring species implies environmental filtering as the primary assembly mechanism, with a minor but increasingly important role of competition towards the present, driven by evolutionary dynamics. Such an increase in the relative contribution of competition to the assembly of communities in relation to the aging of an insular ecosystem, together with a denser packing of morphospace in the early phase of system ontogeny is compatible with ecological predictions according to the theory of island biogeography.

Biological water quality assessment in the degraded Mutara rangelands, northeastern Rwanda - Marie-Claire Dusabe; Torsten Wronski; Guilherme Gomes-Silva; Martin Plath; Christian Albrecht; Ann Apio (Environmental Monitoring and Assessment, 2019)

Geochemical and petrological diversity of mafic magmas from Mount St. Helens - Maren Wanke; Michael A. Clynne; Albrecht von Quadt; Torsten W. Vennemann; Olivier Bachmann (Contributions to Mineralogy and Petrology, 2019)

Climate change impacts in Central Asia and their implications for development - Christopher P.O Reyer; Ilona M. Otto; Sophie Adams; Torsten Albrecht; Florent Baarsch; Matti Cartsburg; Dim Coumou; Alexander Eden; Eva Ludi; Rachel Marcus; Matthias Mengel; Beatrice Mosello; et al. (Regional Environmental Change, 2017)

Climate change impacts in Latin America and the Caribbean and their implications for development - Christopher P.O. Reyer; Sophie Adams; Torsten Albrecht; Florent Baarsch; Alice Boit; Nella Canales Trujillo; Matti Cartsburg; Dim Coumou; Alexander Eden; Erick Fernandes; Fanny Langerwisch; Rachel Marcus; et al. (Regional Environmental Change, 2017)

Biological assessment of water quality and biodiversity in Rwandan rivers draining into Lake Kivu - Torsten Wronski; Marie Claire Dusabe; Ann Apio; Bernhard Hausdorf; Christian Albrecht (Aquatic Ecology, 2015)

Invaders versus endemics: alien gastropod species in ancient Lake Ohrid - Christian Albrecht; Kirstin Föller; Catharina Clewing; Torsten Hauffe; Thomas Wilke (Hydrobiologia, 2014)

A new approach for dating introduction events of the quagga mussel (Dreissena rostriformis bugensis) - Katharina C. M. Heiler; Sascha Brandt; Christian Albrecht; Torsten Hauffe; Thomas Wilke (Biological Invasions, 2012)

The role of barriers and gradients in differentiation processes of pyrgulinid microgastropods of Lake Ohrid - Kirstin Schreiber; Torsten Hauffe; Christian Albrecht; Thomas Wilke (Hydrobiologia, 2012)

Mollusc biodiversity in a European ancient lake system: lakes Prespa and Mikri Prespa in the Balkans - Christian Albrecht; Torsten Hauffe; Kirstin Schreiber; Thomas Wilke (Hydrobiologia, 2012)

Molecular identification, immunolocalization, and functional activity of a vacuolar-type H+-ATPase in bovine rumen epithelium - Elke Albrecht; Martin Kolisek; Torsten Viergutz; Rudolf Zitnan; Monika Schweigel (Journal of Comparative Physiology B, 2008)